FAKTOR YANG MEMPENGARUHI BEHAVIOR INTENTION UNTUK PENGGUNAAN APLIKASI DOMPET DIGITAL MENGGUNAKAN MODEL UTAUT2 - Aries Andrianto (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Based on Bank Indonesia data, electronic money transactions have grown rapidly in the past 10 years. Throughout 2018, the volume of electronic money transactions was 2.92 billion transactions, growing 16,600 times compared to 2009.This study aims to analyze the factors that influence interest in using the LinkAja digital wallet using the UTAUT 2 method. The object of this study is the LinkAja digital wallet user who is domiciled in Jakarta. The independent variables examined in this study were Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, and Habit on Behavior Intention using PLS-SEM analysis techniques. The results of this study indicate that Price Value has a positive effect on Behavior Intention.